Effect of partial replacement of polyphosphate with alkaline electrolyzed water (AEW) on the quality of catfish fillets. (June 2020) - Lin, Hui-Min; Hung, Yen-Con; Deng, Shang-Gui
Abstract: Effect of partial replacement of polyphosphate (50%) with alkaline electrolyzed water (AEW) on the water retention capacity, color, textural properties and lipid oxidation of catfish fillets was investigated. Catfish fillet samples were divided into five soaking group: Group 1 (AEW: pH = 11.6), Group 2 (EOA: AEW with 1.25 g/L sodium tri-polyphosphate, 0.3 g/L sodium metapolyphosphate, 0.4 g/L sodium polyphosphate, pH = 11.4), Group 3 (NEO: water with 2.5 g/L sodium tri-polyphosphate, 0.6 g/L sodium metapolyphosphate, 0.8 g/L sodium polyphosphate, pH = 9.0), Group 4 (WAT: tap water) and Group 5 (NOT: no soaking treatment). The results showed that AEW and EOA can improve catfish fillets weight gain and enhance water retention capacity similar to the phosphate enhancement treatment (NEO), but had no effect on product L* value and hardness and elasticity. For the total color difference (ΔE) and oxidation resistance, EOA treatment was better than AEW and NEO. Therefore, AEW alone or AEW with phosphate used in the traditional phosphate enhancement solutions can be used to enhance the quality of catfish fillets. Highlights: AEW and EOA improve catfish fillets weight gain and water retention capacity. L*, hardness and elasticity of catfish fillets were not affected during storage. For ΔE and oxidation resistance, EOA treatment was better than AEW and NEO. AEW alone or AEW with phosphate can be used to enhance the quality of catfish fillets.